Utilization of matrix‐assisted laser desorption and ionization time‐of‐flight mass spectrometry for identification of infantile seborrheic dermatitis‐causing Malassezia and incidence of culture‐based cutaneous Malassezia microbiota of 1‐month‐old infants. Issue 2 (3rd January 2014) - Yamamoto, Mikachi; Umeda, Yoshiko; Yo, Ayaka; Yamaura, Mariko; Makimura, Koichi
Abstract Matrix‐assisted laser desorption and ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS) has been utilized for identification of various microorganisms. Malassezia species, including Malassezia restricta, which is associated with seborrheic dermatitis, has been difficult to identify by traditional means. This study was performed to develop a system for identification of Malassezia species with MALDI‐TOF‐MS and to investigate the incidence and variety of cutaneous Malassezia microbiota of 1‐month‐old infants using this technique. A Malassezia species‐specific MALDI‐TOF‐MS database was developed from eight standard strains, and the availability of this system was assessed using 54 clinical strains isolated from the skin of 1‐month‐old infants. Clinical isolates were cultured initially on CHROMagar Malassezia growth medium, and the 28S ribosomal DNA (D1/D2) sequence was analyzed for confirmatory identification. Using this database, we detected and analyzed Malassezia species in 68% and 44% of infants with and without infantile seborrheic dermatitis, respectively. The results of MALDI‐TOF‐MS analysis were consistent with those of rDNA sequencing identification (100% accuracy rate). To our knowledge, this is the first report of a MALDI‐TOF‐MS database for major skin pathogenic Malassezia species. This system is an easy, rapid and reliable method for identification of Malassezia.